Clinical Behavior and Treatment Response of Epstein‐Barr Virus‐Positive Metastatic Gastric Cancer: Implications for the Development of Future Trials. (30th April 2020) - Corallo, Salvatore; Fucà, Giovanni; Morano, Federica; Salati, Massimiliano; Spallanzani, Andrea; Gloghini, Annunziata; Volpi, Chiara Costanza; Trupia, Desirè Viola; Lobefaro, Riccardo; Guarini, Vincenzo; Milione, Massimo; Cattaneo, Laura; et al.
Abstract: Background: Epstein‐Barr virus (EBV)‐positive gastric cancers (GCs) have been recently identified as a molecular subgroup showing excellent outcomes after surgery for early‐stage disease and responsiveness to immune checkpoint inhibitors (ICIs) for metastatic stage. No data are available on the prevalence, clinical characteristics, and prognosis of this subgroup of GCs in the metastatic setting. Materials and Methods: In this cohort study, we assessed the impact of EBV status in patients with metastatic GC treated with chemotherapy at two Italian institutions. Results: Among the 175 cases analyzed, only 7 (4%) were EBV positive and all showed long‐lasting and even complete responses to first‐line chemotherapy with fluorouracil and platinum and a significantly better survival compared with EBV‐negative patients (3‐year overall survival: 80% vs. 20.1%; hazard ratio: 0.12). Conclusion: If confirmed in larger data sets, our results may give a strong rationale for investigating the addition of ICIs to chemotherapy, in order to maximize the chance of achieving durable and complete responses in this uncommon subtype of GC. Implications for Practice: To date, no data are available on the prevalence and clinical characteristics of patients with Epstein‐Barr virus (EBV)‐positive metastatic gastric cancer (GC), a specific subtype of GC showing excellent outcomes after radical surgery in early‐stage disease and responsiveness to immune checkpoint inhibitors (ICIs). This cohort study showed that patients with EBV‐positive GC who did not receive ICIs had exceptional, long‐lasting, and even complete responses to first‐line chemotherapy with fluorouracil and platinum and a significantly better survival compared with EBV‐negative patients. If confirmed in larger series, these results may give a strong rationale for investigating the combination of chemotherapy and ICIs to achieve durable and potentially complete response in this uncommon subtype of GC. Abstract : This article assesses the effect of Epstein‐Barr virus status in patients with metastatic gastric cancer.